2017
DOI: 10.13075/mp.5893.00538
|View full text |Cite
|
Sign up to set email alerts
|

Nanogold – Biological effects and occupational exposure levels

Abstract: StreszczenieNanozłoto różni się właściwościami i działaniem biologicznym od złota metalicznego. Może ono znaleźć zastosowanie w wielu dziedzinach, takich jak medycyna, diagnostyka laboratoryjna czy elektronika. Z badań przeprowadzonych na zwierzętach laboratoryjnych wynika, że nanozłoto może się wchłaniać drogą oddechową i pokarmową. Może penetrować w głąb naskórka i skóry właściwej, ale nie ma dowodów, że wchłania się przez skórę. Nanoobiekty złota kumulują się głównie w wątrobie i śledzionie, ale mogą docier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Due to their unique electronic and optical features, gold nanoparticles (AuNPs) have been used for biomarker detection, drug and gene delivery, molecular imaging and photothermal/photodynamic treatment (Boisselier & Astruc, 2009 ; Chen et al, 2007 ; Huang et al, 2007 ; Podsiadlo et al, 2008 ). Accordingly, substantial attention has been paid to the biological effects, toxicity and pharmacokinetics of AuNPs and their interactions with proteins and cells (Świdwińska-Gajewska & Czerczak, 2017 ; Feliu et al, 2016 ; Hornos Carneiro & Barbosa Jr., 2016 ; Wang et al, 2015 ; Araújo et al, 2015 ). Exposure to nanoparticles in pregnancy carries additional risks due to the potential for fetal exposure and teratogenesis or developmental distrurbances; hence, there are growing concerns regarding potential hazards resulting from exposure to nanosized materials in pregnancy (Li et al, 2014 ; Ema et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their unique electronic and optical features, gold nanoparticles (AuNPs) have been used for biomarker detection, drug and gene delivery, molecular imaging and photothermal/photodynamic treatment (Boisselier & Astruc, 2009 ; Chen et al, 2007 ; Huang et al, 2007 ; Podsiadlo et al, 2008 ). Accordingly, substantial attention has been paid to the biological effects, toxicity and pharmacokinetics of AuNPs and their interactions with proteins and cells (Świdwińska-Gajewska & Czerczak, 2017 ; Feliu et al, 2016 ; Hornos Carneiro & Barbosa Jr., 2016 ; Wang et al, 2015 ; Araújo et al, 2015 ). Exposure to nanoparticles in pregnancy carries additional risks due to the potential for fetal exposure and teratogenesis or developmental distrurbances; hence, there are growing concerns regarding potential hazards resulting from exposure to nanosized materials in pregnancy (Li et al, 2014 ; Ema et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic study of the impact of NPs, including AuNPs, on fetal development at different stages of mammalian pregnancy has not yet been carried out. Most studies regarding developmental safety of NPs are focused on mid-term and late pregnancy (Świdwińska-Gajewska & Czerczak, 2017 ; Rattanapinyopituk et al, 2014 ; Balansky et al, 2013 ), namely, the second and third trimester of human pregnancy. Our previous studies found that tail vein injection of AuNPs (0.9 μg Au/g body weight) to pregnant mice from GD5.5 to GD13.5 did not affect fetal survival and offspring health (Yang et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of Ca increases the hardness of alloys, which is related to precipitation hardening. Precious metals, for example, silver, cause the formation of a passive layer, improving corrosion resistance, or gold, which improves corrosion resistance and increases strength and hardness [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. …”
Section: Introductionmentioning
confidence: 99%